UV-activated frontal polymerization of glass fibre reinforced epoxy composites. (15th June 2018) - Sangermano, M.; D'Anna, A.; Marro, C.; Klikovits, N.; Liska, R.
Abstract: In this paper we report, for the very first time, the possibility to UV-crosslink a glass fibre reinforced epoxy composites. We have demonstrated that the crosslinking reaction proceeds via a radical induced cationic frontal polymerization (RICFP), where the UV-surface activation of cationic ring opening polymerization is able to promote the heat front that will activate a thermal initiator in the deeper layers. Because of the very high velocity of the reaction we could obtain quickly epoxy composites maintaining the good thermo-mechanical properties.